Pengaruh Beban Kerja Dan Stres Kerja Terhadap Kinerja Karyawan Selama Pandemi COVID-19 Di PT Business E-Cloud Indonesia - Arrohmah Dwi Novita Sari (2021)
This study is a quantitative study with the aim of knowing and proving the effect of workload and work stress on employee performance during the pandemic at PT Business E-Cloud Indonesia. The population and sample used in this study were 45 permanent employees of PT Business E-Cloud Indonesia. And in testing and processing data using the Smart PLS 3.0 application. The results of this study indicate that (1) workload has a significant positive effect on employee performance during the pandemic, and (2) work stress has a significant positive effect on employee performance during the pandemic.